Development of a Digital Smart Book on Cultural Diversity Material at SMK - Mindie, Amalia Riezka; Susila, Heni Rita; Pebriantika, Leni (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The integration of digital technology in education is essential to enhance student engagement and learning outcomes, particularly in subjects that require contextual understanding such as cultural diversity. However, learning practices in vocational schools are still dominated by teacher-centered approaches and limited use of interactive media, resulting in low student participation and achievement. This study aims to develop and evaluate a Digital Smart Book for cultural diversity material in Pancasila Education at SMK Negeri 03 Ogan Komering Ulu. This research employed a Research and Development (R&D) approach using the ADDIE model integrated with Tessmer’s formative evaluation. The evaluation involved expert validation, one-to-one evaluation, small group evaluation, and field testing. Data were collected through questionnaires and analyzed using descriptive percentages. The results show that the Digital Smart Book is highly valid, with scores of 96.4% from material expert, 85.17% from instructional design expert, and 90.23% from media expert. The product is also practical, as indicated by one-to-one (95.47%) and small group (86.41%) evaluations. Furthermore, the field test result (87.40%) demonstrates its initial effectiveness in improving student engagement. The findings indicate that the Digital Smart Book can serve as an innovative digital learning tool to support student-centered learning in vocational education.